2010
DOI: 10.5513/jcea01/11.1.789
|View full text |Cite
|
Sign up to set email alerts
|

Bioefficacy of Atalantia Monophylla (L.) Correa. Against Earias Vittella Fab.

Abstract: Hexane, chloroform and ethyl acetate extracts of the leaves of Atalantia monophylla (L.) Correa. were evaluated for their antifeedant and larvicidal activities along with their effect on pupation and adult emergence against bhendi fruit borer, Earias vittella Fab. at 5, 2.5 and 1.25% concentrations. Commercial botanical insecticide, Vijay Neem was used as positive control. Hexane extract at 5% concentration showed significant antifeedant and larvicidal activity of 70.89 and 85.33% respectively. A reduction of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
4
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
3
4
0
Order By: Relevance
“…This agreed with the earlier observation of Muthu et al (2010) who reported very low adult emergence was observed in hexane and ethyl acetate extracts of Atalantia monophylla against E. vittella; Baskar et al (2009) observed complete prevention of adult emergence of H. armigera at higher concentration. Further, the fractions from the chloroform extract of Caesalpinia bonduc reduced the emergence of S. litura .…”
Section: Growth Inhibitory Activitiessupporting
confidence: 92%
“…This agreed with the earlier observation of Muthu et al (2010) who reported very low adult emergence was observed in hexane and ethyl acetate extracts of Atalantia monophylla against E. vittella; Baskar et al (2009) observed complete prevention of adult emergence of H. armigera at higher concentration. Further, the fractions from the chloroform extract of Caesalpinia bonduc reduced the emergence of S. litura .…”
Section: Growth Inhibitory Activitiessupporting
confidence: 92%
“…maximum larvicidal activity against S. litura. The present findings coincide with the findings of Muthu et al [15] who noticed that hexane extract of A. monophylla showed 85.33% larvicidal activity at 5.0% concentration against E. vittella. Extracts from Sonchus oleraceus (Asteraceae), Raphanus sativus L. and Brassica nigra L. (Brassicaceae) exhibited larvicidal activity against S. littoralis [22].…”
Section: Crude Extractssupporting
confidence: 82%
“…Present findings coincide with the findings of Baskar et al [14] who reported that hexane extract kill 100% pupae of H. armigera at 5.0% concentration. Muthu et al [15] reported that hexane extract of A. monophylla reduced the adult emergence of E. vittella in a dose dependent manner. Leaves of Ayapana triplinervis (Vahl) R. M. King & H. Rob (Syn.…”
Section: Crude Extractsmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that ethyl acetate extract showed 100% mortality against Anopheles subpictus and Culex tritaeniorhynchus at 1000 ppm concentration and 76% and 71% mortality against Haemaphysalis bispinosa and Paramphistomum cervi, respectively, at 2500 ppm concentrations. Earlier, Muthu et al (2010) reported that ethyl extract of Atalantia monophylla exhibited 78.67% antifeedant activity against Earias vittella.…”
Section: Discussionmentioning
confidence: 99%